Effect of adhesive type and composite viscosity on the dentin bond strength - Batista, Graziela Ribeiro [UNESP] (2015)
Objectives: Evaluate the influence of composite resins viscosity and type of cure of the adhesive systems on the bond strength of composite resins submitted to artificial aging. Methods: Dentin specimens (n = 240) were divided into 2 groups: Group GC: GrandioSO, and Group GF: GrandioSO Heavy Flow. These groups were subdivided into 6: FM: Futurabond M - light cured, FDCC: Futurabond Dual Cure - chemical cured, FDCL: Futurabond Dual Cure - light cured, CS3: Clearfil S3 - light cured, CDCC: Clearfil Dual Cure - chemical cured, and CDCL: Clearfil Dual Cure - light cured. Resin blocks were build up on the dentin surface. Half of samples on each group were cut to obtain resin/dentin sticks (1 × 1 mm). The other half was first submitted to thermomechanical aging. The dentin/resin sticks were submitted to microtensile bond strength test and the results were analyzed using three-way ANOVA and Tukey's test (α = 5%). Results: ANOVA showed significant influence for adhesive (p = 0.0000) and aging (p = 0.0001). No significant influence of the composite viscosity on bond strength was observed (ANOVA: p = 0.0861). For adhesive, the results of Tukey's test (MPa) were CDCC: 13.44 (±5.13)a; FM: 14,01 (±2.71)a; CDCL: 14.51 (±4.98)a; FDCC: 18.66 (±7.13)b; CS3:18.80 (±6.50)b; FDCL: 19.18 (±7.39)b. For aging: AGED: 14.99 (±6.32) a; NOT AGED: 17.87 (±5.97)b. Conclusion: Composite resin viscosities did not influence on the bond strength. Type of cure of the adhesives had influence on the bond strength. Thermomechanical aging decreased the bond strength.